PENGARUH PEMBELAJARAN AKTIF, KEMAJUAN TEKNOLOGI, METODE PEMBELAJARAN, MOTIVASI PESERTA DIDIK TERHADAP PEMBELAJARAN AKUNTANSI: PENGARUH PEMBELAJARAN AKTIF, KEMAJUAN TEKNOLOGI, METODE PEMBELAJARAN, MOTIVASI PESERTA DIDIK TERHADAP PEMBELAJARAN AKUNTANSI - Fitriasari, Pipin (STIE Madani Balikpapan, 2024)
This research aims to determine the influence of active learning, technological advances, learning methods and student motivation in learning accounting. This research is quantitative descriptive research. The objects used in this research were students of SMK Negeri 2 and SMK Negeri 3 Balikpapan. The sampling technique used was non-probability sampling with a sample of 321 respondents. The results of this research show that active learning variables, technological advances, learning methods and participant motivation have a significant influence on accounting learning.